Implementation of Smart City Solution - Zaru, Daniil; Svatá, Vlasta, 1952-; Muknšnábl, Josef; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
This thesis deals with an implementation of a concept called Smart City, which is built on top of the IoT concept. Also, both of the concepts mentioned above are defined in this work including their development over the years and already existing solutions. Besides that, this paper discusses benefits and risks related to these concepts.The main goal of this work is to apply gathered theoretical knowledge on a real example. To do so, a part of the capital of the Czech Republic, Prague 2 is chosen. Status quo of Smart City in Prague is described in the thesis as well as the analysis of efficient opportunities for Smart City solution implementation. Furthermore, the impact on economical, technological, informational and social aspects of the city is covered.
Vedoucí práce: Vlasta Svatá
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: podniková informatika [obor dipl. práce]; diplomové práce; master's theses